Pilot study on ferritin and vitamin D3 levels in early pregnancy and it’s correlation with fetal wellbeing - Chawla, Sushil; Anupama, C. H.; Pitale, Devdatt Laxman; Narendra Jadhav, Sujata (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Overall fetal growth and development is influenced by the maternal nutrition status preconceptionally and in pregnancy. Very few studies have explored the roles of serum ferritin and vitamin D in fetal growth effectively. This pilot study aims to assess the serum Ferritin and vitamin D3 levels in early pregnancy and it’s correlation with fetal wellbeing. Methods: This observational study was conducted at the OBGYN department of tertiary care hospital from Dec 2022 to Dec 2023.A total of 295 pregnant women who satisfied the criteria were recruited. Primary outcome was to assess baseline maternal serum ferritin and Vitamin D3 levels in early pregnancy and secondary outcome to assess it’s effects on fetal wellbeing. Results: Vitamin D deficiency was detected in 21 percent (42) of the study participants and low serum ferritin levels in 20 percent (40) of the patients. Vit D deficiency was more common in primigravidas (15%) as compared to low serum ferritin seen in multigravidas (12.5%). Low Serum ferritin was seen in 15 patients with anaemia and even in 10 patients with Vit D deficiency. Preterm labour, Preeclampsia was seen in three patients. Low birth weight was seen only in 2 patients and the majority of these patients underwent uneventful normal vaginal delivery. Conclusions: Currently limited evidence is available to explore the association of serum ferritin, vitamin D with fetal wellbeing. The present study emphasizes the need for bigger study to elucidate the causal relationship between low maternal serum ferritin and Vitamin D3 and adverse pregnancy outcomes.